2000
DOI: 10.1086/315590
|View full text |Cite
|
Sign up to set email alerts
|

Human Caliciviruses in Acute Gastroenteritis of Young Children in the Community

Abstract: Episodes of acute gastroenteritis in prospectively followed children between 2 months and 2 years of age were examined for rotaviruses, enteric adenoviruses, astroviruses, and human caliciviruses, including both Norwalk-like viruses (NLVs) and Sapporo-like viruses (SLVs), using PCR and reverse transcription (RT)-PCR assays. A virus was identified in 60% (502/832) of all episodes and in 85% of the moderately severe or severe episodes. Human caliciviruses were as common as rotaviruses, both being detected in 29%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
152
4
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(190 citation statements)
references
References 37 publications
27
152
4
7
Order By: Relevance
“…These studies and our results contrast with other sentinel studies conducted by physicians in the general population [5,7,10], in which the incidence of norovirus ranged from 10 to 20%. This is close to and in some cases even higher than the incidence of rotavirus infections [10].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These studies and our results contrast with other sentinel studies conducted by physicians in the general population [5,7,10], in which the incidence of norovirus ranged from 10 to 20%. This is close to and in some cases even higher than the incidence of rotavirus infections [10].…”
Section: Discussioncontrasting
confidence: 99%
“…The literature concerning symptom severity in norovirus and rotavirus gastroenteritis is heterogeneous [42]. A number of previous studies found lower levels of disease severity in norovirus than in rotavirus gastroenteritis, and most of these were carried out in developed countries [7,[43][44][45][46][47]. In contrast, other studies found no significant differences between the severity of rotavirus and norovirus infections [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is that younger pigs are not as susceptible to NoV infection, similar to NoV infections in humans. Noroviruses have been detected in young children between 2 months and 2 years of age [109], but no NoV infections were reported in infants less than 2 months of age. A seroprevalence study of antibodies to Norwalk virus showed that they are acquired gradually in childhood, then more quickly during the adult years and by 50 years of age about 50% of individuals have Norwalk virus antibodies [110].…”
Section: Epidemiology Of Porcine Novs and Savs Prevalence Of Porcimentioning
confidence: 99%